Fra islam e italianità. Nuove seconde generazioni di musulmani nell’Italia monoculturale - Vicini , Fabio (Antropologia Pubblica, 2024)
This paper investigates trajectories of identity formation of “new” second-generation Muslims in northern Italy through the lens of debates on transnationalism, multiculturalism, and multireligiosity. The opening vignette on the conversion of Silvia Romano to Islam is illustrative of how since the 1990s Italian identity has been formulated par opposition to migrants metonymically represented by Islam. Then the article explores the case of the Brescia section of the association Giovani Musulmani d’Italia (GMI) (Young Muslims of Italy) with a focus on the life narratives of three young Muslims. Based on online conversations with members of the association and on information gathered from their social media and online meetings, it discusses seminal works on Muslims in Europe and Italy and argues that the encounter with Muslim associative forms played a key role in their processes of identity formation. As my interlocutors rethink their identities as simultaneously rooted in only apparently contrasting traits such as being Italian, Muslim, and sons of people from a foreign country, their narratives invite us to rethink Italianness in the 21st century. In this regard, the article is an invitation to reflect on the lack of a genuine debate in Italy on the progressively more multicultural and multireligious character of the new generations of Italians. Further, it suggests that anthropology should think of involvement with our interlocutors’ forms of thought as an important kind of public engagement.